Chokeberry (Aronia melanocarpa) as natural antioxidant for the meat industry - Andrea Mesárošová; Marek Bobko; Lukáš Jurčaga; Alica Bobková; Katarína Poláková; Alžbeta Demianová; Judita Lidiková; Ondřej Bučko; Andrea Mendelová; Tomáš Tóth (Czech Journal of Food Sciences, 2024)
Aronia melanocarpa is one of the many fruit types rich in polyphenolic compounds. Therefore, we used this fruit in our research as a possible natural antioxidant, which was added to pork sausages. Four groups were prepared: control group, a group with ascorbic acid, and groups with 3 and 5 mL.kg-1 of chokeberry extract. During storage, we monitored changes in pH, colour, texture and oxidative stability of pork sausages and sensory evaluation. We did not observe any negative effects of the extract on the quality of pork sausages during storage. Regarding oxidative stability, the lowest increase in malondialdehyde (MDA) was observed in the group with 5 mL.kg-1 of chokeberry extract, which was comparable to the group with ascorbic acid.